2003
DOI: 10.1523/jneurosci.23-23-08221.2003
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Interactions between Neurons and Glia Are Required forDrosophilaPeripheral Nervous System Development

Abstract: A major developmental role of peripheral glia is to mediate sensory axon guidance; however, it is not known whether sensory neurons influence peripheral glial development. To determine whether glia and neurons reciprocally interact during embryonic development, we ablated each cell type by overexpressing the apoptosis gene, grim, and observed the effects on peripheral nervous system (PNS) development. When neurons are ablated, glial defects occur as a secondary effect, and vice versa. Therefore glia and neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
78
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(86 citation statements)
references
References 60 publications
(68 reference statements)
8
78
0
Order By: Relevance
“…It has been already noted earlier that expression of Gliotactin is absent in egfr and vein mutants but is expressed in spitz mutants (Sepp and Auld, 2003b). Likewise, it was shown that expression of Neuroglian is dramatically reduced in egfr mutants (Sepp and Auld, 2003b).…”
Section: Discussionmentioning
confidence: 76%
“…It has been already noted earlier that expression of Gliotactin is absent in egfr and vein mutants but is expressed in spitz mutants (Sepp and Auld, 2003b). Likewise, it was shown that expression of Neuroglian is dramatically reduced in egfr mutants (Sepp and Auld, 2003b).…”
Section: Discussionmentioning
confidence: 76%
“…Fly stocks were obtained from the Bloomington Stock Center and the Vienna Drosophila RNAi Center (VDRC), or alternative published sources as noted: P{EPgy2}Eaat1 EY20741 ; Df(2L)30A-C (here denoted Eaat1 Df ); UAS-mCD8::RFP; UAS-Eaat1; UAS-Pros RNAi (VDRC ID 101477); Eaat1-Gal4 (Rival et al, 2004); htl-Gal4 (Shishido et al, 1997); Repo-Gal4 (Sepp and Auld, 2003); tub-Gal80 ts (McGuire et al, 2003); UAS-N ICD (Go et al, 1998); UAS-Hairless (Maier et al, 1999); UAS-Tom (Lai et al, 2000); UAS-Eaat1::GFP (Rival et al, 2004); UAS-mCD8::GFP (Lee and Luo, 1999); UAS-nuclearGFP (van Meyel et al, 2003); Su(H)-lacZ (Griffiths et al, 2007); and fng L73 and fng 13 (Irvine and Wieschaus, 1994;Correia et al, 2003). To create CG31235-nuclear green fluorescent protein (nGFP) and CG31235-Gal4, we PCR amplified 3004 base pairs (bp) of regulatory sequences located immediately upstream of CG31235 using the primers 5Ј-CATAGTGCATTGGTGAGGTGT-3Ј and 5Ј-TACTGGGTGCGCGTTAGGTC-3Ј.…”
Section: Methodsmentioning
confidence: 99%
“…Two additional glial-specific Gal4 drivers were also tested for their ability to rescue Eaat1 SM2/SM2 mutants: Eaat1-Gal4 (Rival et al, 2004) and Repo-Gal4 (Sepp and Auld, 2003), which is expressed more broadly in all lateral glia. Like CG31235-Gal4, these drivers also rescued larval contractions (data not shown).…”
Section: Severe Locomotor Dysfunction In Eaat1 Mutantsmentioning
confidence: 99%
“…Role of localized neurotrophic factor-NRG signaling in peripheral nerve development, maintenance, and disease Although much of the research emphasis in neurotrophic factors has centered on their roles as target-derived factors important for neuronal survival during development, neuronal survival is also highly dependent on glial-derived signals (Sepp and Auld, 2003). Disruption of NRG signaling in mice not only leads to an almost complete loss of Schwann cells, but shortly thereafter, all motor and sensory neurons die.…”
Section: Rapid Axoglial Communication Through Schwann Cell Neurotrophmentioning
confidence: 99%